SF-MAX-Log-MAP parallel decoding algorithm and its application study in LTE - Zengyou Sun; Lijie Zhang; Yong Tian (2011 Cross Strait Triple-Regional Radio Science and Wireless Technology Conference, 2011)
Turbo code, as a kind of LTE encoding scheme, its decoding method has an important influence on its performance and realization. In order to satisfy the low complexity and low delay requirement of LTE decoding, the paper has a combination of SF-MAX-Log-MAP algorithm and parallel decoding, also it carries on the BER performance simulation in LTE system. Simulation results show that: SF-MAX-Log-MAP parallel decoding algorithm, not only is its decoding performance close to the decoding performance of Log-MAP parallel decoding algorithm, but also it reduces the computation process which further reducing decoding delay; it is an efficient algorithm.